2015
DOI: 10.1016/j.jslw.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

What happens to ESL students’ writing after three years of study at an English medium university?

Abstract: The number of international students coming to study in Australian universities has increased exponentially in the past decade, mirroring trends in other English speaking countries. For the majority of these students, English is an additional language. The motivation for studying in an English medium university is presumably not only to gain a degree but also to improve English language proficiency. Studying in an English-medium university provides these students with a rich immersion environment. However, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 31 publications
5
43
1
Order By: Relevance
“…The present findings are also consistent with those of Linnarud (1986) who noted significant differences in lexical sophistication regarding writings by native English speakers and Swedish learners of English and also Laufer (1994) who found significant differences in lexical sophistication between pre-and postwritings performed by two university classes' students. However, this change is inconsistent with Bulte´and Housen (2014), Knoch et al (2015), and Storch and Tapper (2009). For instance, in Bulte´ and Housen's (2014) study, only one out of the three LC measures, namely lexical sophistication, underwent an increase from Time 1 to Time 3, but that increase was not meaningful, and the scores decreased slightly and nonsignificantly over time with respect to lexical density and lexical richness.…”
Section: Discussionmentioning
confidence: 83%
“…The present findings are also consistent with those of Linnarud (1986) who noted significant differences in lexical sophistication regarding writings by native English speakers and Swedish learners of English and also Laufer (1994) who found significant differences in lexical sophistication between pre-and postwritings performed by two university classes' students. However, this change is inconsistent with Bulte´and Housen (2014), Knoch et al (2015), and Storch and Tapper (2009). For instance, in Bulte´ and Housen's (2014) study, only one out of the three LC measures, namely lexical sophistication, underwent an increase from Time 1 to Time 3, but that increase was not meaningful, and the scores decreased slightly and nonsignificantly over time with respect to lexical density and lexical richness.…”
Section: Discussionmentioning
confidence: 83%
“…The investigations done by Storch [11], Knoch, Rouhshad, & Storch [12], Knoch, Roushad, Oon & Storch [13], on the writing development of some undergraduate ESL students in English-medium University for one semester, over one year and three years periods, each found consistent results: that students only achieved fluency and had no gain in accuracy and complexity. The follow-up qualitative research revealed that feedback hadn't done much to improve writing quality related to their majors, because the feedback they could get was related to content only.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Some research also reveals improvement in L2 writing over time, although in different ways depending on the students investigated (Godfrey and Treacy, 2014). On the contrary, studies by Knoch et al (2014Knoch et al ( , 2015 found that the participants´ written performance improvement over time was evident only in the holistic rating, and in fluency not finding any significant changes over time in accuracy or complexity. Different results have also been obtained regarding error development: whereas some studies showed a linear error development, and the same distribution among error types (e.g.…”
Section: Studymentioning
confidence: 99%
“…Recent studies use measures of fluency, accuracy, and complexity to compare writing performance under different conditions (Ghavamnia, Tavakoli & Esteki, 2013), to analyse raters' judgments of various rating measures (Kuiken and Ved-der (2014), or to compare writing performance at different instruction periods (Knoch, Rouhshad & Storch, 2014;Knoch, Rouhshad, Oon & Storch, 2015;Godfrey and Treacy, 2014). Ghavamnia et al (2013:34) conducted a study with forty intermediate EFL learners in order to see if any significant difference existed in the writing performance of the participants under two planning conditions, pre-task planning and online planning in relation to complexity, accuracy, and fluency.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation